Lost and Found - Boland, Bridget (Journal of the Motherhood Initiative for Research and Community Involvement, 2018)
“Lost and Found” explores themes related to miscarriage and the loss of a pregnancy. My husband and I were elated when I became pregnant quickly and easily. That elation turned to despair when I woke on April Fools’ Day to what felt like a cruel joke: I was bleeding at ten-weeks gestation. A sonogram confirmed that the fetus had no heartbeat. I went home and miscarried naturally, without having a dilation and curettage (D&C). We had shared our happy news with family and some friends. Reactions to the miscarriage ranged from helpful support to trite assurances that we could try again. One friend sent a packet of seeds to plant in memory of the baby we’d lost. My mother-in-law, a writer, suggested I see the pregnancy I’d lost as a throwaway “first draft.” Overcome with grief, I first used food to numb my pain. Healing finally came from an encounter with another pregnant mother who had also been through several miscarriages. Her support and shared experience allowed me the opportunity to work through my grief. I turned to tools I’d learned from my yoga practice and my therapist. I created a safe space in which to express my feelings as I hit a pillow with a tennis racket. This somatic expression allowed me to process my emotions instead of sugarcoating them. Despite the pain of my miscarriage, our story had a happy ending when I conceived again, and later gave birth to a healthy baby boy.